Music and the Functions of the Brain: Arousal, Emotions, and Pleasure - Piotr Podlipniak (Frontiers Research Topics, 2018)
Music impinges upon the body and the brain. As such, it has significant inductive power which relies both on innate dispositions and acquired mechanisms and competencies. The processes are partly autonomous and partly deliberate, and interrelations between several levels of processing are becoming clearer with accumulating new evidence. For instance, recent developments in neuroimaging techniques, have broadened the field by encompassing the study of cortical and subcortical processing of the music. The domain of musical emotions is a typical example with a major focus on the pleasure that can be derived from listening to music. Pleasure, however, is not the only emotion to be induced and the mechanisms behind its elicitation are far from understood. There are also mechanisms related to arousal and activation that are both less differentiated and at the same time more complex than the assumed mechanisms that trigger basic emotions. It is imperative, therefore, to investigate what pleasurable and mood-modifying effects music can have on human beings in real-time listening situations. This e-book is an attempt to answer these questions. Revolving around the specificity of music experience in terms of perception, emotional reactions, and aesthetic assessment, it presents new hypotheses, theoretical claims as well as new empirical data which contribute to a better understanding of the functions of the brain as related to musical experience.